Scientometric Dimensions of Neutron Scattering Research in India - Surwase, Ganesh; Kademani, B.S.; Kumar, Vijai (DESIDOC Journal of Library & Information Technology, 2010)
This scientometric study attempts to highlight the Neutron Scattering research in India as per the number of publications appeared in the Scopus database. During the period (1991-2006) a total of 1808 publications were published by the Indian scientists in the field of Neutron Scattering. The average number of publications published per year was 113. The highest number of publications (284) were published in the year 2006. Authorship and collaboration trend was towards multi-authored publications. There were 934 international collaborative publications. India had the highest number of collaborative publications (169, 18.09 per cent) with USA followed by France with 116 (12.42 per cent), Germany with 106 (11.35 per cent), and Japan with 83 (8.89 per cent) publications. The most productive Indian institutions were: Bhabha Atomic Research Centre, Mumbai with 425 publications followed by Indian Institute of Science, Bangalore with 183 publications, Saha Institute of Nuclear Physics, Kolkata with 99 publications and Tata Institute of Fundamental Research, Mumbai with 97 publications. The most preferred journals by the scientists for publication were: Physical Review-B with 129 publications followed by Physical-B with 80 publications, Journal of Physical Chemistry-B with 76 publications, Pramana—Journal of Physics with 75 publications and Journal of Physics Condensed Matter with 51 publications. The high frequency keywords were: neutron scattering (266), micelles (183), surface active agents (104), molecular dynamics (98), phase transitions (96), phonons (84) and small angle neutron scattering (84). The highly cited Indian publications have also been identified. http://dx.doi.org/10.14429/djlit.28.3.173